TafsÄ«r Al-HukamÄâ: Memotret Persinggungan Tafsir Al-Qurâan Dan Tradisi Hikmah - Musadad, Asep N. (Sekolah Tinggi Filsafat Islam Sadra, 2016)
This paper discusses a neglected exegetical tradition in the Qurâanic studies, namely the heritage of âtafsÄ«r al-áºukamÄââ, (tafsÄ«r of the theosophers/áºikmah masters) which is the representation of the áºikmah (theosophical) tradition in the Islamic philosophy. InÂ additionÂ toÂ theÂ studyÂ ofÂ âtafsÄ«rÂ al-falÄsifahâÂ (tafsirÂ ofÂ Hellenistic/Peripatetic philosophers), this heritage is an area of study that needs further exploration in the light of philosophical school of Qurâanic exegesis. It is mainly motivated by the revision of the history of Islamic philosophy in general, that must include âáºikmahâ tradition asÂ theÂ integralÂ part.Â InÂ turn,Â theÂ studyÂ ofÂ QurâanicÂ exegesisÂ shouldÂ alsoÂ correspond with the development of the discourse. Started with a discussion related to the áºikmah tradition,Â thisÂ paperÂ focusesÂ onÂ twoÂ majorÂ issues.Â Firstly,Â itÂ highlightsÂ theÂ contact betweenÂ QurâanicÂ exegesisÂ andÂ áºikmahÂ traditionÂ inÂ aÂ historicalÂ andÂ chronological context. Secondly, it also explains the intersection of both in epistemological relation. ThisÂ researchÂ showsÂ thatÂ throughÂ examiningÂ someÂ QurâanicÂ commentariesÂ written byÂ theolosophersÂ suchÂ asÂ SuhrÄwardÄ«,Â MullÄÂ ShadrÄ,Â upÂ toÂ theÂ currentÂ tradition, the treasury tafsÄ«r hukamÄâ has a rich but still abandoned material. In addition, this traditionÂ alsoÂ hasÂ aÂ distinguishingÂ epistemologicalÂ characteristic compared to other with tafsir traditions.